Apology strategies by Malay learners of English in a Malaysian university - Mohamed Nor, Tun Nur Hamizah; Paramasivam, Shamala (Contemporary Research Center, Australia, 2013)
The purpose of this paper is study the use of apology strategies by Malay tertiary learners of English. The study aims to find out the types of apology strategies used in a variety of communicative situations and to look into the more frequently used strategies. Twenty respondents majoring in English Language were used in the study. A Discourse Completion Task questionnaire of six situations was used to collect data and the SPSS software was used for the analysis. The data was analyzed using a framework of apology strategies culled from the literature. The findings showed that Malay learners employed apology strategies that made up of expressions of apology followed with explanations or reasons for the offence and offers for repairs. The strategies used by the learners reflect the Malay cultural value for harmony and interdependence in interpersonal working relationships. Suggestions are made for future research on apologies.